MEASURING COMPETITIVENESS OF BANKS IN LATVIA - Deniss Krasovskis; Andrejs Limanskis; Erika Pancenko (Copernican Journal of Finance & Accounting, 2017)
Analysis of competition in the banking industry allows to determine the obstacles to its effective functioning. The aim of this research is to analyse the competitiveness level in the modern banking sector of Latvia.